2009
DOI: 10.1101/gad.519709
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy mediates the mitotic senescence transition

Abstract: As a stress response, senescence is a dynamic process involving multiple effector mechanisms whose combination determines the phenotypic quality. Here we identify autophagy as a new effector mechanism of senescence. Autophagy is activated during senescence and its activation is correlated with negative feedback in the PI3K-mammalian target of rapamycin (mTOR) pathway. A subset of autophagy-related genes are up-regulated during senescence: Overexpression of one of those genes, ULK3, induces autophagy and senesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
875
8
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 950 publications
(937 citation statements)
references
References 38 publications
50
875
8
4
Order By: Relevance
“…Furthermore, ATGs promote the efficient secretion of cytokines during oncogene-induced senescence and during cancer cell invasion 106,137 . Further dissecting the cellular mechanisms through which autophagy mediators facilitate these diverse secretory processes remains an important topic for future study.…”
Section: Box 2 | Autophagy and Secretionmentioning
confidence: 99%
“…Furthermore, ATGs promote the efficient secretion of cytokines during oncogene-induced senescence and during cancer cell invasion 106,137 . Further dissecting the cellular mechanisms through which autophagy mediators facilitate these diverse secretory processes remains an important topic for future study.…”
Section: Box 2 | Autophagy and Secretionmentioning
confidence: 99%
“…A recent report showed that autophagy is required for senescence transition in mammalian cells [40].…”
Section: Page 21 Of 59mentioning
confidence: 99%
“…In addition, autophagy is required for chronological lifespan extension in yeast (Alvers et al 2009), and for the longevity response to DR and reduced TOR and insulin signaling in C. elegans, even though its induction alone is not sufficient to extend lifespan (Hansen et al 2008). Inhibiting autophagy triggers premature cellular senescence in human fibroblasts (Kang et al 2011), but it is also required for the senescence transition in response to oncogenic signaling (Young et al 2009), suggesting that autophagy could have pleiotropic effects. Indeed, excessive activation of autophagy can be deleterious and cause cell death independently of apoptosis (Pattingre et al 2005).…”
mentioning
confidence: 99%